Nesiller arası adalete faydacı yaklaşım - (:unkn) unknown (My University, 2012)
Nesiller arası adalet, şimdiki nesil ile yakın ya da uzak gelecekteki nesiller arasında paylaşılan hak ve faydalara atıfta bulunan genel bir kavramdır. Nesiller arasındaki ilişkilerle bağlantılı çalışmalar konuya iki açıdan yaklaşır. Mevcut neslin, olası geçmiş veya olası gelecek nesillerle ilişkilerini ele alır. Her ikisi de şimdi mevcut değildir ve karşılıklı etkileşimin yokluğunda, menfaatlerine saygı gösterip gösterilmeyeceğine karar vermek sadece bizim insiyatifimizdedir. Geçmişte yaşamış olanların menfaatleri eski haksızlıklar yüzünden gündeme gelirken, gelecekle ilgili varsayımlar genelde dağıtıcı adalet ve ekolojik adalet taleplerine dayanır. Bu çalışmada gelecekteki insanlar lehine bir tutum alınacak ve ilgili sorumluluk ya da ödevler faydacı cepheden değerlendirilecektir.

Intergenerational justice is a main concept which refers to the rights and utilities shared between the generations that are existing now and will exist in the near or remote future. The studies concerning the relations among generations mostly deal with the subject from two perspectives. They concern about the relations of present generation with possible past people or possible future people. Both of them are not existing and in the absence of mutual interaction we just have the power of determining whether to show respect to their interests or not. As the interests of past people become a current issue due to the compensation of old injustices, the assumptions about future people are mainly based on the claims of distributive justice or ecological justice. In this paper a position on the interests of future people will be taken and the related responsibilities or duties will be considered from the view of utilitarianism.
The utilitarian approach to ıntergenerational justice
Keywords: Hukuk